2010
DOI: 10.1007/s10750-010-0400-y
|View full text |Cite
|
Sign up to set email alerts
|

Body size in freshwater planktonic crustaceans: an overview of extrinsic determinants and modifying influences of biotic interactions

Abstract: In view of its fundamental and pervasive influences and impacts on organism physiology and ecology, body size is recognized as a key component of evolutionary fitness and serves as the cornerstone of a seminal contribution in freshwater zooplankton ecology-the Size Efficiency Hypothesis (SEH) of Brooks & Dodson (Science 150:28-35, 1965). While the roles and implications of body size in predation and competition-central tenets of the SEH-have been widely considered and reviewed, no broader integrated synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 305 publications
2
96
1
3
Order By: Relevance
“…body size were strongly inversely correlated with fisheries catches in the main zooplanktivorous species (Spearman's rank correlation test between Daphnia sp. claws size and catches; Lake Geneva, q ÂŒ À0.511, P ÂŒ 1.58 3 10 À6 ; Lake Bourget, q ÂŒ À0.340, P ÂŒ 0.009; Lake Annecy, q ÂŒ À0.426, P ÂŒ 0.008; Appendix D), confirming that even though other environmental conditions such as food quality/quantity or temperature (Hart and Bychek 2011) and invertebrate predation (Branstrator 2005), can affect Daphnia sp. body size, they may not be strong enough to compromise the relevancy of using Daphnia sp.…”
Section: Discussionmentioning
confidence: 75%
“…body size were strongly inversely correlated with fisheries catches in the main zooplanktivorous species (Spearman's rank correlation test between Daphnia sp. claws size and catches; Lake Geneva, q ÂŒ À0.511, P ÂŒ 1.58 3 10 À6 ; Lake Bourget, q ÂŒ À0.340, P ÂŒ 0.009; Lake Annecy, q ÂŒ À0.426, P ÂŒ 0.008; Appendix D), confirming that even though other environmental conditions such as food quality/quantity or temperature (Hart and Bychek 2011) and invertebrate predation (Branstrator 2005), can affect Daphnia sp. body size, they may not be strong enough to compromise the relevancy of using Daphnia sp.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, the larger species would be visually preyed on and the small-and medium-sized ones would be preyed on by invertebrates, which are oriented by tactile stimuli. However, it is not always easy to distinguish clear patterns and zooplankton communities are generally composed of medium-sized species (Hart and Bychek, 2011). Furthermore, visual predation is not always determinant in controlling zooplankton, since tactile predation can play the main role (Blumenshine and Hambright, 2003).…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%
“…In contrast, Iglesias et al (2011) suggested that predation by fish is the major factor explaining the smaller size of zooplankton in warm lakes. Hart and Bychek (2011), in their extensive review of the many factors that could potentially influence zooplankton size, addressed extrinsic factors such as temperature, food and predation, amongst others, besides intrinsic ones. The authors concluded, however, that although a general pattern may occur, different results can arise from distinct ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The availability and quality of the biomolecules affects the somatic growth of zooplankton, which is important since the zooplankton body size is directly reflected to its fitness and reproductive output, e.g., the timing of maturity, fecundity, and the survival potential of the offspring (Hart and Bychek, 2011). This is ecologically important because zooplankton have a key position in aquatic food webs by linking the flow of dietary energy and the essential biomolecules from lower (phytoplankton) to upper (fish) trophic levels (Taipale et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%